1-[2-(4-Chlorophenyl)-5-phenyl-2,3-dihydro-1,3,4-oxadiazol-3-yl]ethanone - Hoong-Kun Fun; Suhana Arshad; P. C. Shyma; Balakrishna Kalluraya; T. Arulmoli (Acta Crystallographica Section E, 2012)
In the title compound, C16H14ClN3O2, the 2,3-dihydro-1,3,4-oxadiazole ring [maximum deviation = 0.030 (1) Å] and the pyridine ring [maximum deviation = 0.012 (1) Å] are inclined slightly to one another, making a dihedral angle of 11.91 (5)°. The chloro-substituted phenyl ring is almost perpendicular to the 2,3-dihydro-1,3,4-oxadiazole and pyridine rings at dihedral angles of 86.86 (5) and 75.26 (5)°, respectively. In the crystal, π–π [centroid–centroid distance = 3.7311 (6) Å] and C—H...π interactions are observed.